2019
DOI: 10.1136/bmjoq-2018-000531
|View full text |Cite
|
Sign up to set email alerts
|

Reducing red blood cell folate testing: a case study in utilisation management

Abstract: Mandatory enrichment of wheat flour in Canada with folic acid since 1998 has caused folate deficiency to be rare. There were 3019 red blood cell (RBC) folate tests performed during an 18-month period at London Health Sciences Centre (LHSC)/St. Joseph’s Healthcare London (SJHC) without any folate deficiency detected. We implemented a quality improvement initiative to reduce RBC folate testing at LHSC/SJHC. We began with a retrospective review of RBC folate tests performed during the previous 18 months. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Reductions in provincially funded RBC folate testing are also occurring in Ontario (Ismail et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in provincially funded RBC folate testing are also occurring in Ontario (Ismail et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that applying guidelines and policies of intervention caused a significant reduction of inappropriate requests for laboratory tests ( Ismail et al, 2019 , Pelloso et al, 2016 ). Regrettably, guidelines related to folate and Cobalamin evaluation are widely variable and range from recommending tests for screening of some diseases like dementia to restrictive strategies ( Devalia et al, 2014 , Folate Testing, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…B12 in human serum 00 TOSOH ALA system analyser) and immunoassay method by AIA-2000 Automated Immunoassay Analyzer. Vitamin B12 deficiency was diagnosed if the serum vitamin B12 concentration was < 173 Pg /ml (13) .…”
Section: Methodsmentioning
confidence: 99%